Pengembangan Video Animasi “Vivi dan Jeje” untuk Pembelajaran Menulis Teks Petunjuk bagi Siswa Kelas IV SDN Bunulrejo 3 Malang - Mohamad Vijay; Titis Angga Rini; Puri Selfi Cholifah; Mohamad Vijay; Titis Angga Rini (Universitas Negeri Malang, 2023)
Abstract: This research is based on a preliminary study during KPL (Field Practice Study), interviews with fourth grade teachers, and analysis of the needs of fourth grade students at SDN Bunulrejo 3 Malang, which shows that the use of media is still limited to learning to write instructional texts, so students feel bored. in learning. Based on these problems, an animated video